1991
DOI: 10.1128/mcb.11.10.4943
|View full text |Cite
|
Sign up to set email alerts
|

Induction of NF-kappa B DNA-binding activity during the G0-to-G1 transition in mouse fibroblasts.

Abstract: A DNA-binding factor with properties of NF-KB and another similar activity are rapidly induced when growth-arrested BALB/c 3T3 ceUs are stimulated with serum growth factors. Induction of these DNA-binding activities is not inhibited by pretreatment of quiescent ceUs with the protein synthesis inhibitor cycloheximide. Interestingly, the major NF-KB-like activity is not detected in nuclear extracts of proliferating ceUs, and thus its expression appears to be limited to the Go-to-G1 transition in 3T3 ceUs. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
103
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(113 citation statements)
references
References 66 publications
10
103
0
Order By: Relevance
“…Some have reported that NF-κB activation is necessary to cause cell cycle arrest (Bash et al, 1997). However the body of evidence in recent studies have shown that NF-κB activation is related to cell cycle progression rather than arrest in various cell types (Baldwin et al, 1991;Cressman et al, 1994;Yamada et al, 1997), and that NF-κB inhibition results in cell cycle arrest (Kaltschmidt et al, 1999;Otsuka et al, 1999). Radiation has bi-directional effects on p53; it can activate p53 via ATM (Herzog et al, 1998;Jonathan et al, 1999) and simultaneously activates NF-κB (Li and Karin, 1998), which may have an inhibitory effect on p53 (Stoffel et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Some have reported that NF-κB activation is necessary to cause cell cycle arrest (Bash et al, 1997). However the body of evidence in recent studies have shown that NF-κB activation is related to cell cycle progression rather than arrest in various cell types (Baldwin et al, 1991;Cressman et al, 1994;Yamada et al, 1997), and that NF-κB inhibition results in cell cycle arrest (Kaltschmidt et al, 1999;Otsuka et al, 1999). Radiation has bi-directional effects on p53; it can activate p53 via ATM (Herzog et al, 1998;Jonathan et al, 1999) and simultaneously activates NF-κB (Li and Karin, 1998), which may have an inhibitory effect on p53 (Stoffel et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…NF-KB has a primary role in immune function and inflammation, in lymphoid differentiation, and in embryonic axis determination in insects (Grimm and Baeuerle 1993;Liou and Baltimore 1993;Siebenlist et al 1994;Thanos and Maniatis 1995;Verma et al 1995). There is also evidence that NF-KB plays a role in mitogenic signal transduction (Miyamoto et al 1994) and programmed cell death (Baldwin et al 1991;Beauparlant et al 1994). Furthermore, knockouts of ei ther p50, c-rel, or RelB indicate that NF-KB is critical for specific and nonspecific immune response and cell divi sion (Kontgen et al 1995;Sha et al 1995;Weih et Luciferase activity was determined 24 hr after transfection and the c-Jun transcriptional activity assayed as described in Materials and Methods.…”
Section: Discussionmentioning
confidence: 99%
“…After 24 h, the medium was changed to SFM and the cells were then cotransfected with a plasmid containing the NF-kB-luciferase reporter (a gift from Dr T Gilmore, Boston University, MA, USA) (Baldwin Jr et al, 1991) and pRL-TK-Luc vector, an internal control for transfection efficiency, using Fugene 6 (Roche, Berkeley, CA, USA) according to the manufacturer's procedure. At 48 h after transfection, the cells were lysed for luciferase assay using the Dual-luciferase reporter assay system (Promega, WI, USA).…”
Section: Luciferase Assaymentioning
confidence: 99%